The influence of polystyrene modifier and plasticizer nature on the properties of poly(vinyl chloride) - Levytskyj, Volodymyr; Laruk, Yuriy; Humenetsky, Taras; Sikora, Janusz (Publishing House of Lviv Polytechnic National University, 2015)
Poly(vinyl chloride) (PVC) has been modified by dissolution of polystyrene modifier in diesterphthalate plasticizer, followed by dispersive mixing with PVC. The effects of the kind of modifier and plasticizer used on the wetting of PVC by the plasticizer have been evaluated. The degree of plasticizer migration out of the material and the effects of the migration on mechanical and thermophysical properties of modified materials have been determined. Проведено фізичне модифікування полівінілхлоридних пластикатів, яке включає попереднє розчинення полістирольного модифікатора в диестерфталатному пластифікаторі з подальшим суміщенням з дисперсним полівінілхлоридом. Встановлено і обґрунтовано вплив природи полістирольного модифікатора і диестерфталатного пластифікатора на змочуваність полівінілхлориду пластифікатором, ступінь його мігрування з об’єму матеріалу, а також на пружно-пластичні, міцністні та теплофізичні властивості модифікованих матеріалів.
Вплив природи полістирольного модифікатора й пластифікатора на властивості полівінілхлоридних пластикатів
Keywords: poly(vinyl chloride); migration; plasticization; modification; polystyrene; ABS plastic; полівінілхлорид; міграція; пластифікація; модифікація; полістирол; АБС пластик